Bos, W. & Gröhlich, C. (Hrsg.). (2010). KESS 8. Kompetenzen und Einstellungen von Schülerinnen und Schülern am Ende der Jahrgangsstufe 8. - Schmid, Christoph (Swiss Journal of Educational Research, 2011)
Rezension